Global secretome analysis of resident cardiac progenitor cells from wild‐type and transgenic heart failure mice: Why ambience matters. Issue 7 (21st December 2018) - Samal, Rasmita; Sappa, Praveen Kumar; Gesell Salazar, Manuela; Wenzel, Kristin; Reinke, Yvonne; Völker, Uwe; Felix, Stephan Burkhard; Hammer, Elke; Könemann, Stephanie
Abstract: Resident cardiac progenitor cells (CPCs) have gained attention in cardiac regenerative medicine primarily due to their paracrine activity. In our current study we determined the role of pathological conditions such as heart failure on the autocrine‐paracrine action of stem cell antigen‐1 (Sca‐1) expressing CPC. This comparative secretome profiling of Sca‐1 + cells derived from transgenic heart failure (αMHC–cyclin‐T1/Gαq overexpression [Cyc] cells) versus healthy (wild‐type [Wt] cells) mice, achieved via mass‐spectrometric quantification, enabled the identification of over 700 proteins. Our results demonstrate that the heart failure milieu caused a 2‐fold enrichment of extracellular matrix proteins (ECM) like biglycan, versican, collagen XII, and angiogenic factors like heparan sulfate proteoglycan 2, plasminogen activator inhibitor 1 in the secretome. We further elucidated the direct influence of the secretome on the functional behavior of Sca‐1 + cells via in vitro tube forming assay. Secreted factors present in the diseased milieu induced tube formation in Cyc cells (1.7‐fold; p  < 0.01) when compared with Wt cells after 24 hr of exposure. The presence of conditioned media moderately increased the proliferation of Cyc cells but had a more pronounced effect on Wt cells. Overall, these findings revealed global modifications in the secretory activity of adult Sca‐1 + cells in the heart failure milieu. The secretion of ECM proteins and angiogenic factors, which are crucial for cardiac remodeling and recovery, was notably enriched in the supernatant of Cyc cells. Thus, during heart failure the microenvironment of Sca‐1 + cells might favor angiogenesis and proliferation suggesting their potential to recover the damaged heart. Abstract : In our current study we determined the role of pathological conditions such as heart failure on the autocrine‐paracrine action of stem cell antigen‐1 (Sca‐1) expressing CPC using mass‐spectrometric quantification. The secretion of ECM proteins and angiogenic factors, which are crucial for cardiac remodeling and recovery, was notably enriched in the supernatant of Cyc cells and was shown to improve tube formation.